Optimalisasi Perkembangan Anak Prasekolah melalui Tidur Sehat, Omega 3, dan Stimulasi Sesuai Usia (TOSS) - Eka Wahyuningrum; Andrea Putri Sekar Tunjung; Andri Kenti Gayatina (Poltekita: Jurnal Pengabdian Masyarakat, 2026)
The golden age refers to a crucial period in a child's growth and development. Optimal child development is essential for children to be better prepared for school. A preliminary study revealed that 12 of the 18 children at Imanuel Christian Kindergarten experience suspect based on Denver II examination. Appropriate efforts from healthcare professionals are needed to anticipate further problems resulting from delays. This Community Service (PkM) aimed to increase parental knowledge about age-appropriate stimulation, healthy sleep, and omega-3, and to optimize the development of preschool children through snakes and ladders play therapy. Parents received counseling on the theme "Healthy Sleep, Omega-3, and Stimulation for Preschool Child Development" using lecture and Focus Group Discussion (FGD) methods. Children received TOSS (Healthy Sleep, Omega-3, and Age-appropriate Stimulation) play therapy in three groups. The PkM results showed an increase in knowledge scores about age-appropriate stimulation, healthy sleep, and Omega-3 between before and after attending the counseling (a 3.93 increase in knowledge). Most parents (10 parents) experienced an increase in knowledge. The results of the observations showed that most of the children felt happy, enthusiastic, and followed instructions well, although some children initially had difficulty focusing and wanted to play in their own way.